Teachers and school administrators’ experiences with professional development feedback: The classroom strategies assessment system implementation - Poulou, Maria S.; Reddy, Linda A.; Dudek, Christopher M. (Frontiers in Psychology, 2023)
To support teachers’ evaluation and professional development valid assessments that measure teachers’ classroom practices and capture teachers’ strengths and areas in need of improvement are needed. The current study examined school administrators’ and teachers’ experiences of Professional Development (PD), with the use of the Classroom Strategies Assessment System (CSAS), a classroom observational assessment that measures universal classroom instructional and behavioral practices, and their perceptions of the usability of CSAS for supporting PD. The study also examined school administrators’ ratings of elementary school teachers’ use of evidence-based instructional and behavior management practices, as an illustrative example of how performance feedback was implemented. Three school administrators observed 31 elementary school teachers three times each using the CSAS Greek version. Following each observation, teachers received brief performance feedback based on CSAS scores from their school administrator. School administrators and teachers completed the System Usability Scale (SUS) to assess the usability of the CSAS administration. Semi-structured interviews with 19 of the participating teachers were conducted to further explore teachers’ professional development experiences. Overall, teacher interviews expressed their need for professional development in the areas of instructional and behavior management practices and perceived CSAS feedback helpful for instructional improvement. Findings also suggest some improvements in the frequency and quality of teacher instructional and behavior management practices as measured by the CSAS. Implications for practices and research are discussed.